PENGARUH PEMBERIAN LARUTAN HASIL FERMENTASI BERBASIS CAMPURAN BAHAN ORGANIK TERHADAP PERTUMBUHAN SELADA MERAH (Lactuca sativa L.) VARIETAS RED RAPID - Itsna Safira Ridwan (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2022)
The purpose of this research is to get concentration of fermented solution based on a mixture of organic material which gave the highest effect on the growth of red lettuce (Lactuca sativa L.) Red Rapid varieties. The research method used is an experimental method with a single factor Randomized Block Design (RBD) with 8 treatments and 4 replications, the treatments: A0 (concentration of fermented solution 0 ml/l), A1 (concentration of fermented solution 100 ml/l), A2 (concentration of fermented solution 200 ml/l), A3 (concentration of fermented solution 300 ml/l), A4 (concentration of fermented solution 400 ml/l), A5 (concentration of fermented solution 500 ml/l), A6 (concentration of POC NASA 6 ml/l), and A7 (dose of NPK fertilizer 250 kg/ha). The results showed that there was a significant effect of giving fermented solution based on a mixture of organic material on the average plant height of 7 dap, 14 dap, 21 dap, 28 dap, and 35 dap and the average number of leaves 35 dap. The treatment of A7 (dose of NPK fertilizer 250 kg/ha) obtained the highest results to the average plant height of 7 dap, 14 dap, 21 dap, 28 dap, and 35 dap, meanwhile the treatment of A2 (concentration of fermented solution 300 ml/l) obtained the highest results to the average number of leaves.